2001
DOI: 10.1074/jbc.m105826200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Binding of an SRF/NK-2/MEF2 Transcription Factor Complex in Normal Versus Neoplastic Smooth Muscle Tissues

Abstract: The malignant potential of smooth muscle tumors correlates strongly with the disappearance of ␥-smooth muscle isoactin, a lineage-specific marker of smooth muscle development. In this paper, we identify a 36-base pair regulatory motif containing an AT-rich domain, CArG box, and a non-canonical NK-2 homeodomainbinding site that has the capacity to regulate smooth muscle-specific gene expression in cultured intestinal smooth muscle cells. Serum-response factor associates with an NK-2 transcription factor via pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 74 publications
(125 reference statements)
0
30
0
Order By: Relevance
“…5). Prior studies indicate that normal cultured smooth muscle cells show a decrease in the expression of SRF as differentiation progresses from day 1 myoblast to day 10 myocyte (Phiel et al, 2001). In contrast to controls, Urp treatment of smooth muscle cells at 50, 100, and 100 pM resulted in the maintenance of high levels of SRF expression throughout the 10-day culture period, while 1,000 pM of Urp resulted in a pattern of SRF expression similar to that observed in controls (Fig.…”
Section: Urotensin Ii-related Peptidementioning
confidence: 57%
See 1 more Smart Citation
“…5). Prior studies indicate that normal cultured smooth muscle cells show a decrease in the expression of SRF as differentiation progresses from day 1 myoblast to day 10 myocyte (Phiel et al, 2001). In contrast to controls, Urp treatment of smooth muscle cells at 50, 100, and 100 pM resulted in the maintenance of high levels of SRF expression throughout the 10-day culture period, while 1,000 pM of Urp resulted in a pattern of SRF expression similar to that observed in controls (Fig.…”
Section: Urotensin Ii-related Peptidementioning
confidence: 57%
“…These findings are the first to suggest a potential connection between Urp expression and bladder smooth muscle development. Normal bladder smooth muscle development initiates with mesenchymal compaction around embryonic day 15 in mice, and appears unique in its spatial patterning from other smooth muscle tissues (Phiel et al, 2001;McHugh, 1995). In contrast, developing mgbϪ/Ϫ bladders show a lack of mesenchymal condensation resulting in independent clusters of differentiating smooth muscle myoblasts widely separated by regions of undifferentiated mesenchyme .…”
Section: Discussionmentioning
confidence: 99%
“…6 Several studies have shown a correlation between human cancer and elevated levels of SRF or SRF binding to CArG boxes. [99][100][101][102] Whether such increases in SRF are causative or merely reflective of human cancer is unclear. Recently, however, the liver-restricted miR-122 was shown to be attenuated in human hepatocellular carcinomas where SRF levels are elevated.…”
Section: Srf and Cancermentioning
confidence: 99%
“…Nkx2-5 belongs to the NK-2 homeobox family and has been implicated in myocardial development, in both cardiomyocytes and smooth muscle (76). In an in vitro model of smooth muscle differentiation, the promoter of the smooth muscle gamma isoactin gene has been shown to bind NK-2 and serum response factor in intestinal smooth muscle cells (57). In uterine smooth muscle cells myocyte enhancer factor 2 is also bound in this complex (57).…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro model of smooth muscle differentiation, the promoter of the smooth muscle gamma isoactin gene has been shown to bind NK-2 and serum response factor in intestinal smooth muscle cells (57). In uterine smooth muscle cells myocyte enhancer factor 2 is also bound in this complex (57). Previous studies have also reported the upregulation of several transcription factors associated with the transition from pregnant not-in-labor to laboring myometrium in rat, mouse and human (8,16,25,28,32,53,62,69).…”
Section: Discussionmentioning
confidence: 99%